Evaluation of gravity‐led and energy‐fed drainage for sustaining food security in the polders of the coastal zone of Bangladesh. (5th March 2022) - Mondal, Manoranjan K.; Yadav, Sudhir; Baidya, Bishwajit; Khan, Zahirul H.; Sutradhar, Asish; Humphreys, Elizabeth; Kamal, Farhana A.; Jagadish, S. V. Krishna
Abstract: Bangladesh is currently self‐sufficient in rice production but faces immense challenges of sustaining that self‐sufficiency because of population growth and climate change. There is little scope to further increase cropping intensity except in the underutilized 1.2 Mha of lands enclosed in the polders of the coastal zone. The main impediment to wide‐scale adoption of more productive cropping systems in the polders is poor drainage that often results in waterlogging. Therefore, a study was conducted in polder 30, in the medium‐salinity region of the south‐west coastal zone, to examine the biophysical and economic feasibility of low‐cost gravity (gravity‐led) drainage. The results show a considerable opportunity to increase rice production in the polders with improved drainage practices. The feasibility of drainage through pumping (energy‐fed) was also assessed, given that there are already situations where gravity‐led drainage is not feasible, and these situations are likely to increase because of climate change‐induced sea level rise and the sinking of polder lands. Energy‐fed drainage was demonstrated to be profitable with a yield gain of at least 1.5 t/ha from just the wet season; further intensification to 50% of polder lands may yield an additional harvest of 3–6 million tons of rice per year. Therefore, investing in improved drainage management in the polders could be a major game changer in sustaining the food security of the nation, especially the climate‐vulnerable polder communities of Bangladesh. Résumé: Le Bangladesh est actuellement autosuffisant en riz mais est confronté à d'immenses défis pour maintenir cette autosuffisance en raison de la croissance démographique et du changement climatique. Il y a peu de possibilités d'accroître davantage l'intensité de culture, sauf dans les 1, 2 Mha de terres sous‐utilisées enclavées dans les polders de la zone côtière. Le principal obstacle à l'adoption à grande échelle de systèmes de culture plus productifs dans les polders est le mauvais drainage qui entraîne souvent l'engorgement. Par conséquent, une étude a été menée dans le Polder 30, dans la région de salinité moyenne de la zone côtière du sud‐ouest, pour examiner la faisabilité biophysique et économique du drainage gravitaire à faible coût (par gravité). Les résultats montrent une opportunité considérable d'augmenter la production de riz dans les polders avec des pratiques de drainage améliorées. La faisabilité du drainage par pompage (alimenté en énergie) a également été évaluée, étant donné qu'il existe déjà des situations où le drainage par gravité n'est pas réalisable, et ces situations sont susceptibles d'augmenter en raison de l'élévation du niveau de la mer induite par le changement climatique et le naufrage des polders. Le drainage énergétique s'est avéré rentable avec un gain de rendement d'au moins 1, 5 t/ha à partir de la seule saison des pluies; une intensification supplémentaire à 50% des terres des polders peut donner une récolte supplémentaire de 3 à 6 millions de tonnes de riz par an. Par conséquent, investir dans une meilleure gestion du drainage dans les polders pourrait changer la donne dans le maintien de la sécurité alimentaire de la nation, en particulier les communautés des polders vulnérables au climat du Bangladesh.